2018
DOI: 10.1002/ghg.1766
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of cyclic carbonate via the coupling reaction of carbon dioxide with epoxide at ambient pressure

Abstract: Cyclic carbonates were synthesized via the coupling reaction of CO2 with epoxides at ambient pressure. The reaction of atmospheric pressure CO2 with styrene oxide (SO) was selected as the model reaction. The coupling reaction was investigated by varying a simple catalytic system composed of Lewis acid and quaternary ammonium salt, molar ratio of catalyst to substrate, solvent, and temperature. The yield of styrene carbonate (SC) reached 91.5% in the presence of ZnBr2/Bu4NBr at p(CO2)° = 0.1 MPa and 100°C for 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…In summary, the results showed that the highest yield, at 91%, was obtained using epichlorohydrin as substrate and TBAB as a cocatalysts, and a slight decrease in the catalytic activity was observed in the presence of other epoxides under the same reaction conditions (Table 6, entries 1, 3–4). These results show that the increase in the electron‐donating properties of the substituents of the oxirane ring decreases the catalytic activity slightly under the same reaction conditions as previously reported 38,39 …”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…In summary, the results showed that the highest yield, at 91%, was obtained using epichlorohydrin as substrate and TBAB as a cocatalysts, and a slight decrease in the catalytic activity was observed in the presence of other epoxides under the same reaction conditions (Table 6, entries 1, 3–4). These results show that the increase in the electron‐donating properties of the substituents of the oxirane ring decreases the catalytic activity slightly under the same reaction conditions as previously reported 38,39 …”
Section: Resultssupporting
confidence: 86%
“…These results show that the increase in the electron-donating properties of the substituents of the oxirane ring decreases the catalytic activity slightly under the same reaction conditions as previously reported. 38,39…”
Section: Substrate Scopementioning
confidence: 99%
“…[2,3] Compared to carbon capture and storage( CCS) techniques, carbon capturea nd utilization (CCU) techniques are more attractive, ast he captured CO 2 can be effectively converted to various valuable productss uch as urethanes, formic acid, dimethyl carbonate, and cyclic carbonates. [11][12][13][14][15][16][17][18][19][20] Cyclic carbonates are highly stable compounds; thus, long-term sequestration of CO 2 is possible. [11][12][13][14][15][16][17][18][19][20] Cyclic carbonates are highly stable compounds; thus, long-term sequestration of CO 2 is possible.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10] Ap rominent CO 2 fixation method is the atom-efficient cycloadditiono fe poxides to CO 2 to produce industrially and economically importantf ive-membered cyclic carbonates. [11][12][13][14][15][16][17][18][19][20] Cyclic carbonates are highly stable compounds; thus, long-term sequestration of CO 2 is possible. Moreover, cyclic carbonates have received extensive attention as solvents in Li-ion batteries, as monomers forp olymer synthesis, and their utility in the productiono fp olyurethanes, chemical products, and fuel additives.…”
Section: Introductionmentioning
confidence: 99%